FORMULATION AND ANTIBACTERIAL ACTIVITY TEST OF COCOA BEAN EXTRACT TOOTHPASTE (Theobroma Cacao L.) AGAINST STREPTOCOCCUS MUTANS BACTERIA - Apriliani Margaret Marista Lourina Rarung; Paulina Yamlean; Karlah Mansauda (UNIVERSITAS SAM RATULANGI, 2022)
Cocoa beans (Theobroma cacao L.) are seeds of the cocoa tree which have a active components, is polyphenols which have the potential as antibacterial. This study aimed to formulate the toothpaste of Cocoa bean ethanol extract with concentrations of 5%, 7.5%, 10%, 12.5%, 15% and tested for physical evaluation of the preparation and to obtain the inhibitory power against Streptococcus mutans bacteria. In this research, the cocoa beans was extracted used the maceration method with 96% ethanol solvent and tested for antibacterial used the well method. The results showed an organoleptic physical evaluation requirements, homogeneous homogeneity test, pH test 7.4-7.7, spreadability test 30-33 mm, and adhesion test 2.25-3.23 seconds. Toothpaste has antibacterial activity with an average diameter of F1 (8.16 mm), F2 (8.5 mm), F3 (9.5 mm), F4 (10.41 mm) are in the medium category and F5 (11.58 mm) is in the strong category. Based on the study result can be concluded that all formulations of toothpaste preparations of Cocoa bean ethanol extract filled the antibacterial activity requirements and physical test requirements and had the strongest antibacterial activity at a concentration of 15% at 11.58 mm.